Humans of New York - Stanton, Brandon (New York : St. Martin's Press, 2013)
"Based on the blog with more than a million loyal fans, a beautiful, heartfelt, funny, and inspiring collection of photographs capturing the spirit of a city. In the summer of 2010, photographer Brandon Stanton set out on an ambitious project: to single-handedly create a photographic census of New York City. Armed with his camera, he began crisscrossing the city, covering thousands of miles on foot, all in an attempt to capture New Yorkers and their stories. The result of these efforts was a vibrant blog he called "Humans of New York," in which his photos were featured alongside quotes and anecdotes. The blog has steadily grown, now boasting more than a million devoted followers. Humans of New York is the book inspired by the blog. With four hundred color photos, including exclusive portraits and all-new stories, Humans of New York is a stunning collection of images that showcases the outsized personalities of New York. Surprising and moving, printed in a beautiful full-color, hardbound edition, Humans of New York is a celebration of individuality and a tribute to the spirit of the city. With 400 full-color photos and a distinctive vellum jacket"--
"In the summer of 2010, photographer Brandon Stanton set out on an ambitious project: to single-handedly create a photographic census of New York City. Armed with his camera, he began crisscrossing the city, covering thousands of miles on foot, all in his attempt to capture ordinary New Yorkers in the most extraordinary of moments. The result of these efforts was "Humans of New York," a vibrant blog in which he featured his photos alongside quotes and anecdotes. The blog has steadily grown, now boasting nearly a million devoted followers. Humans of New York is the book inspired by the blog. With four hundred color photos, including exclusive portraits and all-new stories, and a distinctive vellum jacket, Humans of New York is a stunning collection of images that will appeal not just to those who have been drawn in by the outsized personalities of New York, but to anyone interested in the breathtaking scope of humanity it displays. Heartfelt and moving, Humans of New York is a celebration of individuality and a tribute to the spirit of a city"--
Communication, intercorporeity, and responsibility : for a new approach to humanism -- Global communication, global semiotics, and globalization -- Dialogism, intercorporeity, and modeling -- The semiotic animal, semioethics, and responsibility -- Global semiotics, cognitive semiotics, and semioethics -- Toward a critique of identity: on signs, bodies, and values -- Dialogism and otherness: the critical task of semioethics -- Global communication and its risks -- Is there a way out? -- Signs of difference : from identity to unindifferent difference -- Migration, unemployment, and globalization -- The extracommunitarian other -- Transcultural communication, ideology, and social planning -- From reason to reasonableness : a semioethic approach to subjectivity -- Listening, hospitality, restitution -- Redefining the subject -- Otherness and intercorporeity -- Mother-sense : an a priori for subjectivity, signification, and critique -- Semioethics and humanism of the other, a way out -- From reason to reasonableness -- Sense and expression -- The open society of open selves -- Communication, language, and speech from a global perspective -- Moving toward global semiotics -- Remembering and -- Nothing that is a sign is alien to me -- On biosemiotics and its recent history -- Signs and life : the Gaia hypothesis -- Signs and nonsigns -- Icon, index, and symbol -- Communication and speech -- Communication among others -- Homologies and analogies in zoosemiosis -- Totality and otherness -- Otherness and nomination -- Semiosis with language and semiosis without language -- Otherness, dialogism, and interpretation -- On sign and communication models -- The dialogic nature of signs and understanding -- Subjectivity and interpretation -- More contributions to symbolicity, indexicality, and iconicity -- Firstness, secondness, and thirdness -- Signs, inference, and evolutionary forces in the universe -- Signs to talk about signs -- Speech, language, and modeling -- Semiotic materiality, sign typologies, and inference -- Linguistic production, ideology, and otherness : contributions from philosophy of language -- Philosophy of language : scope, method, and itineraries -- Linguistic production, ideology, and creativity -- "End of ideology!" -- From decodification to interpretation -- For a dialogic approach to sign and subjectivity -- Philosophizing about language from the viewpoint of literature -- Binarism, triadism, and dialogism.
Keywords: Street photography -- New York (State) -- New York; City and town life -- New York (State) -- New York -- History -- 21st century -- Pictorial works; Photography, Artistic; New York (N.Y.) -- Pictorial works